STRATEGI BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KOTA DUMAI DALAM PENANGGULANGAN BENCANA BANJIR DI KOTA DUMAI TAHUN 2021 - Sabella Marshanda; Rury Febrina (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The city of Dumai has always been plagued by flood problems until now, the coverage of flood areas is still spread throughout the city. For this reason, a Dumai City BPBD strategy is needed so that flood problems can be overcome. Extreme weather such as high rainfall is a trigger factor for flooding. The floods that occurred in Dumai City from 2019 to 2021 have made people always worry about flood disasters. This study intends to formulate the Dumai City BPBD strategy in flood disaster management and the efforts of the Regional Disaster Management Agency (BPBD) in handling it. The research location is in Dumai City, precisely at the Dumai City Regional Disaster Management Agency (BPBD) on the basis of the consideration that floods often occur in this area. This study uses the theory of strategy put forward by Fred R. David, namely strategy formulation, strategy implementation, and strategy evaluation that enables an organization to achieve its goals. Using a descriptive qualitative approach. Data collection techniques through interviews and documentation. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions or verification. The results showed that the strategy implemented by BPBD Dumai City in the form of program activities, namely disaster prevention and preparedness services and disaster victim rescue and evacuation services had not run optimally in flood disaster management. One of the obstacles in the implementation of the disaster management program is the limited budget and minimal human resources in the field. Then, the condition of the Dumai City area has mostly shallow river areas so it is very prone to natural disasters in the form of flooding, especially during the rainy season. Of the various forms of strategy carried out also serves to increase public awareness and preparedness towards disaster. Keywords: Strategy, BPBD, Mitigation, Flood, City of Dumai